COACHING CLINIC OLAHRAGA TONNIS BAGI MAHASISWA STKIP MELAWI - Hadiana, Oman; Eko Rudiansyah; Nur Kusuma Atmaja; Sartono (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
This Community Service activity aims to introduce and deepen STKIP Melawi students' understanding of the game of tennis starting from equipment and other supporting equipment, playing techniques and game rules. This PkM is carried out on the basis of achievements for playing tonnis in Melawi Regency and there are very few seeds in the sport of playing tonnis because there are many obstacles in the formation of tennis players due to the lack of socialization and introduction to the community about tonnis. The benefit of this service is that STKIP Melawi students have a new reference for teaching small ball games in learning, besides that tennis can also be used in the educational curriculum at school.